PENERAPAN METODE SYSTEMATIC LAYOUT PLANNING UNTUK MEMINIMASI JARAK PERPINDAHAN MATERIAL PADA UKM X - Inna Kholidasari; Yulia Sridewi Syahri; Susanti Sundari (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
Proper layout arrangements can have an impact on minimizing the distance and time of the production process. The research was conducted at UKM X which produces fish-based snacks in Jambi Province where there is a back and forth flow in work activities due to the placement of work stations that are not in the order of the process flow and the placement of each process in a different room resulting in an increase in both working time and distance required in the production process. The purpose of this research is to re-design the layout of production process facilities in minimizing the distance between production processes by applying the Systematic Layout Planning (SLP) method. The results of this study indicate that the percentage of reduced material movement distance in the initial layout with the proposed alternative layout I is 21.56% (the selected proposed layout) and in the proposed II alternative layout is 15.94%. And the results of this study can be used as a guideline for UKM X managers which are used as case studies in research..